Identifikasi Kadar Fenol dan Flavonoid Ekstrak Etanol Rimpang Kunyit (Curcuma longa L.) - Antonius Purba (Herbal Medicine Journal, 2019)
Turmeric rhizome is an herbal medicine, in herbal medicine, many types of diseases that can be cured such as, inflammatory, tumour, cancer prevention, and others. This study was aimed to determine the total levels of phenols and flavonoids in ethanol extract of turmeric rhizome (Curcuma longa L.). The method for making this extract was done by maceration using 96% ethanol. Qualitative analysis of phenols and flavonoids was performed by UV-Vis Spectrophotometry. Determination of phenol levels using Folin ciocalteau reaction and determination of total flavonoid levels was carried out by the colorimetric method with quercetin comparison. The result showed that phytochemical screening of turmeric rhizome (Curcuma longa L.) contains alkaloids, flavonoids, tannins, and saponins. The results of the determination of levels of turmeric rhizome ethanol extract were obtained a total phenol 229,0894 mg GAE / g and total flavonoid 140,0666 mg QE / g extract.